Overview of The Use of The National Student Fitness Test in Schools - Yudhidwi Nusantara; Kurnia Eka Wijayanti; Sucipto (Universitas Negeri Semarang, 2025)
The National Student Fitness Test is an evaluation instrument developed by the Ministry of Youth and Sports (Kemenpora) to assess the physical fitness levels of Indonesian students. However, its implementation in schools still faces several challenges, particularly the lack of optimal integration with physical education learning. This study aims to describe the implementation of The National Student Fitness Test in schools. This research uses a quantitative descriptive methods. The sample used in this research was physical education teachers in Lembang sub-district. Data analysis used descriptive statistics to present percentage distributions. The results indicate that most teachers (70.6%) have implemented national student fitness test, and its overall application is categorized as good, especially in terms of preparation (85.48%) and assessment accuracy (82.24%). Nevertheless, the main challenges were found in administrative procedures (65.48%) and in the utilization of assessment results (68.60%). In addition, teachers expressed very high expectations regarding the development of a digital-based national student fitness test system (90.80%). The study concludes that the implementation of national student fitness test in schools has been adequate in terms of preparation and assessment accuracy, but it still faces obstacles related to administration and the use of assessment outcomes. The strong expectation for national student fitness test digitalization highlights the need for a more efficient and accurate system to support the management of fitness data. Strengthening teacher competence and developing an integrated digital platform are therefore essential steps to optimize the role of national student fitness test in evaluating and planning physical education learning in schools.